Upper central incisors with periapical lesions treated with two integrated endodontic systems: a six-month randomized controlled trial - Daniele Angerame; Matteo De Biasi; Vittorio Franco; Lorenzo Bevilacqua; Attilio Castaldo (Ariesdue, 2016)
Aim: To assess preliminarily the success rate of the root canal treatment with two integrated shaping and filling systems of upper central incisors with chronic periapical pathosis. Methodology: Sixty adult subjects with an untreated maxillary central incisor presenting a chronic periapical lesion smaller than 5 mm in diameter were recruited for the present study. The patients were randomly divided into two treatment groups: G1 (n = 30), Revo-S/One Step Obturator; G2 (n = 30) GTX/GTX Obturator. All root canal treatments were performed in a single session by the same operator. Sensitivity to palpation and percussion was registered at baseline and at the six-month recall. Radiographic healing was scored by two blind examiners according to a previously described scale. The absence of statistically significant differences in terms of baseline clinical parameters between the two groups was assessed by means of a Mann-Whitney test (age, apical gauging) and χ2 test (sensitivity to percussion and palpation). The radiographic scores attributed to the two groups were compared with a Mann-Whitney test, while a χ2 test served to compare the clinical data gathered after six months (p < 0.05). Results: Baseline clinical parameters registered in the two groups were found to be comparable. All patients attended the six-month recall and all the teeth were referred to be negative to sensitivity, with the exemption of two subjects per group. The periapical lesions were scored as totally healed, partially healed and not healed in 43.4%, 53.3% and 3.3% of cases in G1 and in 43.3%, 50.0% and 6.7% of cases in G2. The differences between the groups were not significant. Conclusions: Tough cases scored as incomplete healing should be further followed up, the present study attests that the two tested integrated shaping and filling systems are capable of high and comparable six-month success rate in upper central incisors with periapical pathosis.